Drag measurements of fluttering fabrics and their application for sportswear - Fuss, F. K. (Sports Engineering, 2024)
Loose and baggy clothing is required by the rules of ski cross and snowboard cross. However, it is known from the literature that fluttering garments increase the aerodynamic drag. The aim of this study was to investigate the influence of flexural rigidity and fabric weight on the coefficient of drag CD. Eleven fabrics (550 mm long, 320 mm wide) with different flexural rigidity (0.016-99 µNm) and fabric weight (0.1-2.4 N/m2) were tested in a wind tunnel on a cylinder (width 325 mm, diameter 125 mm) at speeds of 25 to 120 kph (Reynolds numbers Re 60 k-280 k). The general trend showed that fluttering fabrics that are heavier and stiffer create more drag force. All but one fabric had a smaller CD than the bare cylinder in the subcritical flow regime (CD ˜ 1.1), at least within a Re window of 80 k. One fabric had a consistently higher CD (average: 1.27) than the bare cylinder. The mean CD value of the other ten fabrics ranged from 0.87 to 1.07, with minimum CD values between 0.76 and 1. The CD advantage of the ten fabrics ended at the beginning of the critical flow regime of the bare cylinder between Re 200 k and 220 k. A regression analysis showed that the magnitude of the CD is more influenced by the flexural rigidity of a fabric, normalised to its weight, than by the weight itself, at least at Re < 250 k. The results of this study suggest that ski and snowboard cross athletes` suits should be made from light and flexible fabrics to reduce aerodynamic drag.